Bioanalysis of urine samples after manipulation by oxidizing chemicals: technical considerations. (June 2014) - Fu, Shanlin; Luong, Susan; Pham, Annie; Charlton, Nathan; Kuzhiumparambil, Unnikrishnan
Drug testing programs are established to help achieve a drug-free work environment, promote fair competition in sport, facilitate harm minimization and rehabilitation programs, better manage patient care by clinicians and service law enforcement authorities. Urine remains the most popular and appropriate testing matrix for such purposes. However, urine is prone to adulteration, where chemicals, especially oxidizing chemicals, are purposely added to the collected urine specimens to produce a false-negative test result. This article will describe the effect of various popular oxidizing adulterants on urine drug test results, the countermeasures taken by laboratories in dealing with adulterated urine samples and the prospect of developing more robust and economical methods to combat urine adulteration in the future.